Physical properties of the multiphase ionic-plasma coatings - Jurov, V.M.; Laurinas, V.Ch.; Guchenko, S.A.; Zavatskaya, O.N. (Publishing House of the KarSU named after E.A.Buketov, 2013)
The article includes the following topics: obtaining coatings in the conditions of deposition of multicomponent plasma flow and study the structure of the obtained coatings; the influence of ion and laser irradiation on the structure and properties of multiphase coatings. A direct impact on the structure and physical properties of coatings obtained by ion-plasma deposition, provide the following parameters, which are determined experimentally: the pressure of a reactive gas in the working chamber; potential basis; discharge current of the arc; the properties of the material of the cathode; the temperature of the substrate. Work is executed under the program of Ministry of education and science of the Republic of Kazakhstan 055 «Scientific and/or scientific-technical activities», subprogramme 101 «Grant funding for research».
Keywords: multiphase ionic-plasma coatings; technological parameters; electron - microscopic images; microhardness